Better Students Ask More Questions.
f(x) = ax^3+bx^2-4x-3, where a and b are constants.It is given that (x-1) is a factor...
2 Answers | add yours
Best answer as selected by question asker.
`f(x) = ax^3+bx^2-4x-3`
Since (x-1) is a factor we can say f(1) = 0
`f(1) = 0`
`f(1) = a(1)^3+b(1)^2-4xx1-3`
`0 = a+b-7`
`a+b = 7`
So the requirement is shown.
a+b = 7
Posted by jeew-m on May 25, 2013 at 8:57 PM (Answer #1)
Join to answer this question
Join a community of thousands of dedicated teachers and students.